Natural Gas and Israel's Energy Future - Popper, Steven W.; Berrebi, Claude; Griffin, James; Light, Thomas; Min, Endy Y. (RAND Corporation, 2023)
This book discusses the opportunities and risks the government of Israel faces in shifting to a greater reliance on domestic and imported natural gas. By applying newly developed methods for strategic planning and decisionmaking under deep uncertainty, the analysis seeks to help the Israeli government engage in managed change by choosing robust strategies that minimize potential consequences of relying more heavily on natural gas.